Efeito in vitro da Triiodotironina (T3) na diferenciação osteogênica e condrogênica das células tronco do tecido adiposo de equinos - Débora de Oliveira Spila (2019)
The addition of hormones, growth factors, vitamins, among others additives to cultures of mesenchymal stem cells (MSC) aims to increase proliferation, induce differentiation and decrease the time of culture. In addition, MSC with greater osteogenic or chondrogenic potential are cells with greater ability to synthesize, in vitro, mineralized and cartilaginous matrix, respectively. The effect of triiodothyronine (T3) addition to MSC cultures under osteogenic and chondrogenic differentiation has already been tested with good results in rat and human cells. Thus, one hypothesis is that the use of stem cells with greater potential for osteogenic or chondrogenic differentiation could increase the chances of recovery or accelerate the treatment of diseases or alterations affecting bone and cartilage tissues, respectively. The objective of this study was to evaluate the effect of T3 in two concentrations (0,01nM and 1000nM) compared to the control group in the osteogenic and chondrogenic differentiation of the adipose tissue MSC-AT in horses. In the first experiment, the effect of T3 on the osteogenic differentiation of the MSC-AT, based on the results of the alkaline phosphatase (ALP); mitochondrial metabolism, cell density and matrix produced by the MSC-AT was measured by the amount of mineralized nodules at seven, 14 and 21 days. In the second experiment, the effect of T3 on the chondrogenic differentiation of the MSC-AT was evaluated, based on the results of the alkaline phosphatase activity; of mitochondrial metabolism; of the cell density and the percentage of chondrogenic matrix were performed at 7 and 14 days in culture. In both experiments, ANOVA was performed with comparison of the means by the SNK test. Differences between groups were considered significant if p<0.05. In the first experiment, at seven days, there were no differences between groups with respect to any of the variables studied. At 14 days, the lower concentration of T3 (0,01nM) reduced cell density and number of mineralization nodules, although increased ALP activity and mitochondrial metabolism. The higher concentration of T3 (1000nM) increased ALP activity without altering the number of mineralized nodules compared to the control. At 21 days, the lower concentration of T3 increased ALP activity without altering the other parameters in comparison to the control. The higher concentration of T3 (1000nM) reduced the conversion of MTT to formazan and cell density without altering the number of mineralization nodules in comparison to the control. In the second experiment, at seven days, the two concentrations of T3 significantly increased the cell density in comparison to the control without altering the other parameters studied. At 14 days, the higher concentration of T3 (1000nM) reduced the mitochondrial metabolism, ALP activity, cell density and percentage of chondrogenic PAS +13 matrix compared to control. It is concluded that the addition of T3 to equine MSC-AT cultures does not increase osteogenic or chondrogenic differentiation and may even cause negative effect under cell density and matrix synthesis, depending on the concentration of the hormone and the time of culture.